EFISIENSI KERJA WHEEL LOADER KOMATSU WA 200-5 DI PABRIK BRIKET TANJUNG ENIM PT. BUKIT ASAM Tb - Derisman, Aken; Sarmidi; Zikri (Fakultas Teknik UMRI, 2022)
Based on business development in the Tanjung Enim Briquette work unit related to the production of Activated Carbon and Carbon Anodes, to support production, work efficiency is needed on the heavy equipment unit, namely Wheel Loaders. In addition, by obtaining work efficiency data, it is possible to evaluate the work of the wheel loader in its operations at the Tanjung Enim Briquette Factory PT. Bukit Asam Tbk. So that there is an increase and optimization of the work/operational quality of the Wheel Loader to achieve the production target. At the Tanjung Enim Briquette factory itself the wheel loader unit plays an important role in supporting the production of Carbonized Briquettes, Non-Carbonized and serves various types of work in the briquette factory such as filling hopper, material mixing or blending, transporting clay and loading raw coal stock. The data collection process for 16 days started on August 2 until August 27, 2021 with the average wheel loader working efficiency of 86.12% in the good category.